(untitled) (KULT_online, 2015)
This collection of essays explores events in Kyiv (Kiev) and Crimea in 2013/14 and their historical, social, political, cultural, and legal contexts. The seventeen multi-disciplinary contributions, covering sociology, history, media studies, international relations, political science, and law, are by academics and non-academics, including journalists, activists, legal experts, and policymakers. The Polish National Research Centre (NCN) sponsored the publication, thus most authors are Polish-based, although scholars from the US, UK, Sweden, and Germany also contribute. Bachmann and Lyubashenko edited the volume into August 2014, while the texts reach President Petro Poroshenko’s election on 25 May 2014. The editors claim they "wanted the book to be an intervention during the crisis" (p. 17).